2023
DOI: 10.1111/srt.13457
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis to reveal the potential comorbidity mechanism in psoriasis and nonalcoholic steatohepatitis

Ningyi Xian,
Ruimin Bai,
Jiaqi Guo
et al.

Abstract: PurposeAn increasing amount of evidence suggests that psoriasis and nonalcoholic steatohepatitis (NASH) may occur simultaneously, whereas the underlying mechanisms remain unclear. Our research aims to explore the potential comorbidity mechanism in psoriasis and nonalcoholic steatohepatitis.Materials and MethodsThe expression profiles of psoriasis (GSE30999, GSE13355) and NASH (GSE24807, GSE17470) were downloaded from GEO datasets. Next, common differently expressed genes (DEGs) of psoriasis and NASH were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…This persistent inflammation is a key factor behind the characteristic hives, itching, and symptoms seen in CU and other skin infections. 22 Our study suggests that in CU, the body experiences persistent triggers like allergens, infections, or auto-immune reactions, leading to an overproduction of TNF-alpha. This excess release can contribute to a sustained immune response, potentially increasing inflammation and skin-related symptoms.…”
Section: Discussionmentioning
confidence: 74%
“…This persistent inflammation is a key factor behind the characteristic hives, itching, and symptoms seen in CU and other skin infections. 22 Our study suggests that in CU, the body experiences persistent triggers like allergens, infections, or auto-immune reactions, leading to an overproduction of TNF-alpha. This excess release can contribute to a sustained immune response, potentially increasing inflammation and skin-related symptoms.…”
Section: Discussionmentioning
confidence: 74%
“…It is worth mentioning that the study by Xian et al. demonstrated that IFIT1 and IRF9 are important genes linking psoriasis and nonalcoholic steatohepatitis, 22 and obesity has been proven to be a risk factor for nonalcoholic steatohepatitis 23 . Therefore, PI3 may also be an important link between obesity and nonalcoholic steatohepatitis.…”
Section: Discussionmentioning
confidence: 98%
“…As a systemic disease, psoriasis is also related with many diseases and numerous studies have already established the relationship between psoriasis and other diseases like depression, nonalcoholic steatohepatitis, and IBD 36–41 . Our previous work focused on the comorbidity mechanism between psoriasis and nonalcoholic steatohepatitis, and identified several key genes as potential therapeutic targets using bioinformatics methods 42 . This discovery not only aids in understanding the comorbidity mechanisms of these two diseases but also emphasizes the broader applicability of bioinformatics in revealing complex disease relationships.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40][41] Our previous work focused on the comorbidity mechanism between psoriasis and nonalcoholic steatohepatitis, and identified several key genes as potential therapeutic targets using bioinformatics methods. 42 This discovery not only aids in understanding the comorbidity mechanisms of these two diseases but also emphasizes the broader applicability of bioinformatics in revealing complex disease relationships. Ding et al suggested that FOS may play a critical role in both IBD and psoriasis, contributing to a growing body of evidence supporting the genetic commonality between these diseases.…”
Section: Shokrollah Et Al Have Shed Light On Potential Novel Biomarke...mentioning
confidence: 93%